Government Takeovers of U.S. Foreign Affiliates - Hawkins, Robert G.; Mintz, Norman; Provissiero, Michael (Journal of International Business Studies, 1976)
This article examines the characteristics of takeovers by foreign governments of 170 American firms in the post-war period. The dimensions observed include the frequency by subperiod; industry of the firm; degree of discrimination against foreign and U.S. firms of the takeovers; the form of the takeover; and the political circumstances in the host country at the time of takeover. Summary measures for each of the characteristics and their changes through time are presented.